Uncertainty in regional climate model outputs over the Czech Republic: the role of nested and driving models. (14th February 2013) - Holtanova, Eva; Kalvova, Jaroslava; Pisoft, Petr; Miksovsky, Jiri
Abstract In this study, we present a comparison of relative influence of the structure of regional climate model (RCM) and its driving global climate model (GCM) on the variance of surface air temperature and precipitation simulated by a multi‐model ensemble in the area of the Czech Republic. RCM outputs from the project ENSEMBLES are incorporated and compared to RCM outputs from the project PRUDENCE. We show results for 30‐year mean seasonal surface air temperature and precipitation for the reference period (1961–1990) and two future time periods (2021–2050 and 2071–2100), and the changes of these quantities in the future period in comparison to the reference period. We have found that the influence of GCM on the variance of both multi‐model ensembles is larger in case of changes of mean seasonal surface air temperature than for the mean values in corresponding time periods. We cannot make any similar general conclusion for precipitation. The results for the ENSEMBLES models are different from the results obtained for the PRUDENCE models in some aspects, especially for mean seasonal surface air temperature and precipitation in the end of the 21st century. Copyright © 2013 Royal Meteorological Society